2010
DOI: 10.1039/b927263a
|View full text |Cite
|
Sign up to set email alerts
|

First principles study of doped carbon supports for enhanced platinum catalysts

Abstract: Highly oriented pyrolytic graphite (HOPG) implanted with N, Ar and B is studied as a support for platinum nanoparticle catalysts for fuel cells. Experimentally, we find that Pt supported by N-HOPG is more disperse, more catalytically active and suffers less particle ripening than native HOPG, while Pt supported on Ar-irradiated HOPG is slightly more active but ripens more than Pt on native HOPG. Defective HOPG supports are modeled by density functional theory (DFT) calculations that confirm and explain the abo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
128
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(138 citation statements)
references
References 20 publications
10
128
0
Order By: Relevance
“…A rst principles study reported that pyrrolic and pyridinic N offered the defect site for the in situ nucleation and growth of Pt NPs due to the induced partial charges on neighboring carbon atoms. 32,39 An improved performances toward ORR of mesoporous N-doped carbons containing mainly quaternary Ngroups was highlighted as a result of the chemical interaction between Pt NPs and N-defects. 40 Besides, pyridinic and graphitic N acted as active sites for contributing to the ORR performances.…”
Section: Resultsmentioning
confidence: 99%
“…A rst principles study reported that pyrrolic and pyridinic N offered the defect site for the in situ nucleation and growth of Pt NPs due to the induced partial charges on neighboring carbon atoms. 32,39 An improved performances toward ORR of mesoporous N-doped carbons containing mainly quaternary Ngroups was highlighted as a result of the chemical interaction between Pt NPs and N-defects. 40 Besides, pyridinic and graphitic N acted as active sites for contributing to the ORR performances.…”
Section: Resultsmentioning
confidence: 99%
“…Chemical modification of the graphene lattice by heteroatom doping is a common way to form anchor sites in graphene. The N-doping of graphene supports can reportedly increase the dispersion of Pt catalysts [15] and prevent Pt agglomeration [16,17]. This improves the catalyst durability and efficiency for the ORR, compared with that of pristine graphene supports.…”
Section: Introductionmentioning
confidence: 97%
“…N doping also provides nucleation sites 29 as well as enhances Pt activity, stability and durability. 30,31 Platinized nanowires with high platinum dispersions benefiting from the surface heterogeneity and functionality are compared with commercial catalysts in Table V and the corresponding X-ray diffractograms are shown in Figure 8. Here, a 14 wt% Pt on P-PPy sample PL (Pt-PL) possesses ∼1.9 nm Pt particles, smaller than the commercial catalysts.…”
Section: Resultsmentioning
confidence: 99%